The ak’aat k’aal movement among the Aari people of south-west Ethiopia - Naty, Alexander; Kaneko (ed.), Morie; Shigeta (ed.), Masayoshi (Aethiopica, 2006)
Students of African studies have reported a variety of religious movements under the rubric of independent churches. These include the Cherubim and Seraphim, the Church of the Lord, the Church of Simon Kimbangu, the Zionist and Ethiopianist’s independent churches in southern Africa. Most of these churches emerged in those countries that were under European colonial domination. Ethiopia did not experience European colonialism. Indeed, imperial Ethiopia conquered militarily less powerful kingdoms and chiefdoms that were located to the south and south-western of the then Abyssinia. The conquest of formerly independent populations in southern Ethiopia during the late nineteenth century introduced unequal power relations between the indigenous people and the new settlers. This paper examines the evolution of a religious movement referred to as ak’aat k’aal among the Aari people of south-west Ethiopia in the context of the indigenous forms of domination. Although the movement was short-lived, it was meant to enable the Aari to cope with the social psychological stress that the serfdom system generated. The Aari were not able to practice their traditional religion because of the serfdom. Therefore, they had to abandon their religion. However, doing this without finding a substitute was incompatible with Aari religious ideology. The ak’aat k’aal was a substitute just for a short period. ATTENTION: Due to copy-right no online publication is provided.